2020
DOI: 10.47405/mjssh.v5i4.388
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness for the World of Work Among Malaysian Diploma Students in a Local Institution

Abstract: The purpose of this study is to investigate the use of appraisal system-attitude and cooperative solidarity principle and also the perception of interviewees and interviewer of the job interview interactions. The data was collected in one of the local education institutions in Kuala Lumpur Malaysia. There were 20 students participated in the study. Job interviews were recorded and analysed qualitatively by using appraisal system-attitude and cooperative solidarity principle theories. Semi-structured interviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Based on extensive literature search, we found that studies on English language acquisition in the Malaysian context have been mainly carried out on Malaysian tertiary learners and graduates (e.g. Isai et al 2020;Mohd Zin, Eng, and Rafik-Galea 2014;Sarudin et al 2013;Ting et al 2017;Turiman, Abdullah, and Mohd Noor 2018;Zainuddin et al 2018). We posit that to understand the underlying cause of Malaysian learners' English performance, studies investigating learners' development at the earlier level, such as at the preschool levels, are necessary.…”
Section: Preschool and English Language Education In Malaysiamentioning
confidence: 99%
“…Based on extensive literature search, we found that studies on English language acquisition in the Malaysian context have been mainly carried out on Malaysian tertiary learners and graduates (e.g. Isai et al 2020;Mohd Zin, Eng, and Rafik-Galea 2014;Sarudin et al 2013;Ting et al 2017;Turiman, Abdullah, and Mohd Noor 2018;Zainuddin et al 2018). We posit that to understand the underlying cause of Malaysian learners' English performance, studies investigating learners' development at the earlier level, such as at the preschool levels, are necessary.…”
Section: Preschool and English Language Education In Malaysiamentioning
confidence: 99%
“…Other researchers, such as Edmund (2015) and Karim (2016), also noted that poor language proficiency was a barrier to employment, and reports revealed that over 40,000 Malaysian graduates from public universities could not secure jobs in the private sector because of language problems (Davies et al, 2020;Mustafa, 2018;Rasul et al, 2010). Davies et al (2020) and Krishnan et al (2020) suggested there was a real need to establish a standard of proficiency for fresh graduates who were seeking to enter the Malaysian workforce.…”
mentioning
confidence: 99%